Glucagon-like peptide-1 receptor agonists as add-on therapy to insulin for type 1 diabetes mellitus - Tan, Xinrui; Pan, Xiongfeng; Wu, Xiaochuan; Zheng, Songjia; Chen, Yuyao; Liu, Donghai; Zhang, Xingxing (Frontiers in Pharmacology, 2023)
Background: To assess the efficacy and safety of glucagon-like peptide-1 receptor agonists (GLP-1 RAs) used as an adjunct to insulin therapy in adults with type 1 diabetes. Methods: A search of electronic databases (Medline, Embase, and the Cochrane Central Register of Controlled Trials) from 1 January 1950 to 23 May 2021 was conducted to find randomized controlled trials. The primary outcome was the change in HbA1c. Eight efficacy and six safety secondary endpoints were evaluated via meta-analysis. Weighted mean difference (WMD) and odds ratio (OR), alongside 95% confidence interval (CI), were calculated using the random effects model. Results: Among 1379 candidate studies, 11 trials comprising 2856 participants satisfied the inclusion criteria. Overall, GLP-1 RA adjunctive therapy reduced HbA1c by –0.21% (95%CI, –0.33 to –0.10), weight by –4.04 kg (–4.8 to –3.27), systolic pressure by –2.57 mmHg (–4.11 to –1.03), and diastolic blood pressure by –1.02 mmHg (–1.99 to –0.06). In addition, there was a decrease in prandial insulin dose (WMD, –4.23 IU; 95%CI, –5.26 to –3.20), basal insulin dose (–2.40 IU; –3.93 to –0.87), and total insulin dose (–5.73 IU; –10.61 to –0.86). Moreover, GLP-1 RAs did not increase the incidence of severe hypoglycemia, diabetic ketoacidosis, or severe adverse events. However, GLP-1 RAs increased the incidence of gastrointestinal adverse events (OR, 2.96; 95%CI, 2.33 to 3.77). Conclusion: Our meta-analysis of randomized clinical trials suggests moderate beneficial effects of GLP-1 RAs on the metabolic profile in patients with type 1 diabetes, without an increased risk of serious adverse events.